Interpersonal Communication and Sor Theory in “TASTE” Market Snacks in Increasing Customer Loyalty - Kurniawan, Dani; Ifani, Muhammad Zulfi; Nurfaizi, Kevin Rohman (Journal of Language and Health, 2023)
Communication is one of the main foundations in running a business. Communication needs to be established to establish relationships between businesses and their customers (Fathurohman & Safitri, 2020). This is intended as a means to find out how to communicate with customers and create product sales targets that suit consumer desires. Based on the existing background, this research aims to analyze interpersonal communication using social theory in the "RASA" market snack in increasing customer loyalty. This research model is qualitative in the form of field research. Primary data is the main data obtained through interviews, namely interviews with the sales manager of the "RASA" market snacks. Furthermore, secondary data will be obtained from documentation whose function is to support research to make it more accurate. Then this research uses the stimulus organism response (SOR) theory approach. In this research is that interpersonal communication has a strategic role in business development, being an effective means of changing the attitude of someone who starts as a consumer and continues to become a customer. With the SOR theory, it can be seen that interpersonal communication can be used as a strategy in implementing communication to change attitudes from consumers to customers. Customer retention is also influenced by friendliness, trust and product quality, the first impression of which is the main thing in running a business.